STUDI KASUS MENGENAI KECERDASAN EMOSIONAL DAN TIPE KEPRIBADIAN PADA BIDAN PRAKTIK MANDIRI - Eka Rasyid Deatri (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
A midwife is one who is engaged in the profession of public services, especially health. Interest and demand for the services of a midwife continues to increase every year, especially in Indonesia. Midwifery profession itself is a profession with a very heavy job demands, including the welfare and safety of patients. In addition, midwives are also required to perform its role as a wife and homemaker. Both of these roles must be lived well. Therefore, a midwife should be able to maintain her physical and psychological condition, otherwise it can caused stress, fatigue, physical or psychological disorders, or can even jeopardize a patient safety. The demand characteristics and capabilities expected of a midwife in Psychology concepts is integrated in the emotional intelligence concept. The importance of all the capabilities which should be owned by a midwife looks more in line with the concept described by Bar-On who explained emotional intelligence as a synergy between the five large-scale, namely the ability of intrapersonal, interpersonal, adaptability, stress management and general mood. In addition, the type of personality is also considered to have an important role in the profession of midwifery in addition to emotional intelligence. The purpose of this research is to examine the emotional intelligence and personality type of midwives who practice independently. The study was conducted with a qualitative approach by the case study method with 3 participants. This study uses the Bar-On Emotional Quotient Inventory (EQ-i) measurement tool, which contains 133 items to measure five aspects of emotional intelligence and the NEO PI-R personality measurement tool as well as an interview guide. The results show that emotional intelligence plays an important role in all three participants profession. All three participants have a good understanding of the concept of emotional intelligence, but all three do not apply well in their work or in everyday life, they intended to show their personality type which is contrast to their understanding of the emotional intelligence concept.